Teknik Pembibitan Tanaman Kelor (Moringa oleifera Lam) dalam Rangka Penyediaan Sumber Pangan Sehat Berkelanjutan di Desa Gumantar Lombok Utara - Bambang Budi Santoso; I Nyoman Soemeinaboedhy S; Jayaputra Jayaputra (Jurnal SIAR ILMUWAN TANI, 2020)
In the context of realizing, maintaining and improving the highest public health status, community service activities was carried out in the form of extension activities. The target object of community service activities in the form of counseling on Moringa oleifera Lam seedling nursery techniques in the context of providing healthy food sources in Gumantar Village, North Lombok Gumantar Village, Kayangan District, North Lombok Regency, especially members of the Telaga Valley Farmers Group, and the Hamlet Amor-Amor apparatus. The activity that carried out was one of the services to the community, namely the delivery of information through teaching and discussions as well as demonstrations of Moringa plant nursery techniques. To see whether farmers are responsive to the material that was presented, on this occasion it was observed from the feedback or response to questions asked by farmers during the discussion after the material was delivered and also the level of enthusiasm of the participants in practicing the method of Moringa plant nursery. The results shows that there was an increase in the understanding and knowledge of the members of the Valley of Telaga farmer groups regarding the benefits of the Moringa plant as a source of healthy food and a versatile plant. Increased knowledge on plant nursery techniques to produce good quality moringa seedlings, and resulted in vegetative and generative brochures for moringa plant nurseries.